The olphabet : "O" no! an alphabet revolt - Brallier, Jess M.; Cowdery, Nichola (Philadelphia : RP Kids, 2021)
Tiring of an alphabetic order that relegates her to the middle, the Letter O repositions herself at the beginning of a newly dubbed "olphabet" before revisiting her subsequent letter friends to figure out where she truly belongs.
Keywords: Picture books; Alphabet -- Juvenile fiction